2007
DOI: 10.1111/j.1468-2508.2007.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Same Facts, Different Interpretations: Partisan Motivation and Opinion on Iraq

Abstract: Scholars assume that citizens perform better when they know pertinent facts. Factual beliefs, however, become relevant for political judgments only when people interpret them. Interpretations provide opportunities for partisans to rationalize their existing opinions. Using panel studies, we examine whether and how partisans updated factual beliefs, interpretations of beliefs, and opinions about the handling of the Iraq war as real-world conditions changed. Most respondents held similar, fairly accurate beliefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
315
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(335 citation statements)
references
References 11 publications
13
315
1
6
Order By: Relevance
“…For such valence issues, the interpretation of numeric information through a partisan lens is likely to be less salient (Gerber and Green 1998). In contrast, partisan biases may be more important for ideologically-charged issues such as immigration (Druckman, Peterson and Slothuus 2013) or welfare policy (Slothuus and De Vreese 2010), where there is also greater scope for a disjuncture between fact-based beliefs and interpretations (Gaines et al 2007). …”
Section: Voter Sophisticationmentioning
confidence: 99%
See 1 more Smart Citation
“…For such valence issues, the interpretation of numeric information through a partisan lens is likely to be less salient (Gerber and Green 1998). In contrast, partisan biases may be more important for ideologically-charged issues such as immigration (Druckman, Peterson and Slothuus 2013) or welfare policy (Slothuus and De Vreese 2010), where there is also greater scope for a disjuncture between fact-based beliefs and interpretations (Gaines et al 2007). …”
Section: Voter Sophisticationmentioning
confidence: 99%
“…In contrast with more ideological issues, where individual partisanship is likely to moderate voter beliefs and interpretations of the information that they receive (e.g. Druckman, Peterson and Slothuus 2013;Gaines et al 2007;Jerit and Barabas 2012;Zaller 1992), voters are more likely to internalize information about valence issues like unemployment when they deem such information credible.…”
mentioning
confidence: 99%
“…For cases like these, citizens who are habitual online or central route processors -often dubbed by political scientists as issue votersare likely to have preferences before the study begins; those available for persuasion are likely to consist disproportionately of less motivated, memory-based evaluators. 6 These considerations 5 In studies that do not distinguish on-line from memory-based processing, the typical pattern is rapid decay of persuasion effects (Gaines, Kuklinski, and Quirk, 2007). A study following this pattern but not cited is de Vreese (2004, p. 203).…”
Section: Laboratory and Internet Studies Of Persuasionmentioning
confidence: 99%
“…14 Public support for war is often thought to be based on perceptions of costs, benefits and likelihood of success. However, recent studies have shown that average citizens are unable to accurately assess war costs (Baum & Groeling, 2010;Berinsky, 2007Berinsky, , 2009Cobb, 2007;Gaines, et al, 2007;Myers & Hayes, 2010). Our findings thus far offer one reason why: information about casualties is difficult to come by in the American public sphere.…”
Section: Insert Figure 2 About Herementioning
confidence: 70%